Flexible multilayered aramid nanofiber/silver nanowire films with outstanding thermal durability for electromagnetic interference shielding. (December 2021) - Li, Shuang; Qian, Kunpeng; Thaiboonrod, Sineenat; Wu, Hongmin; Cao, Shaomei; Miao, Miao; Shi, Liyi; Feng, Xin
Highlights: Multilayered ANF/AgNW films were prepared by alternate filtration process. Multilayers significantly improved EMI shielding and mechanical properties. Multilayered films with 7-layer structure exhibited high EMI SE of 63.3 dB. The films with ANF as outer layers displayed superior thermal durability of 400 °C. Abstract: Multilayered aramid nanofiber/silver nanowire (ANF/AgNW) films using AgNW as internal conductive layers and ANF as outer protective layers were fabricated via a multiple filtration layer-by-layer process and subsequent hot-pressing. The electromagnetic interference (EMI) shielding and mechanical properties of the multilayered ANF/AgNW films were significantly improved through hydrogen bonding between adjacent layers, and EMI shielding properties were accordingly enhanced owing to the internal multiple reflection of electromagnetic waves between AgNW layers. The 7layer structure ANF/AgNW films exhibited excellent mechanical properties with a tensile strength of 79 MPa and fracture strain of 4.6%, high EMI shielding effectiveness of 63.3 dB, attributing mainly to the synergetic effect of intrinsic mechanical strength of ANF and excellent electrical conductivity of the tightly interconnected AgNW network. In addition, the multilayered films which have excellent stability for EMI shielding properties at high temperature (∼400 °C) are better than traditional polymer-based EMI shielding materials.